Adsorption of Methylene Blue on Activated Charcoal, Silica Gel and Silica - Saeed, Rehana; Uddin, Fahim; Summer, Shazia (Asian Journal of Chemistry, 2016)
Adsorption of methylene blue from aqueous solution has been investigated on activated charcoal, silica gel and silica (clay) by spectrophotometric method. Langmuir and Freundlich plots were drawn and their constants were evaluated from the relevant data, which determined the mechanism and the nature of forces involved in adsorbate-adsorbent interactions. Correlation coefficients of the entire data in connection with Langmuir and Freundlich plots for each adsorbent were also calculated. It was found that these regression coefficients approach 99% in most cases, which rather signifies the validity of the data for the straight line. An attempt has also been made to calculate the surface area of the adsorbent.